Outcomes After Open Reduction With Internal Fixation of Mandible Fractures. Issue 5 (July 2018) - Barry, Rahman G.; Wolbert, Thao T.; Gress, Todd W.; Ray, Peter D.; Mozaffari, Farid B.
Abstract : Introduction/Hypothesis: Mandible fractures contribute substantially to morbidity after blunt trauma. Controversy exists surrounding the appropriate timing of surgical intervention and benefit from routine postreduction imaging. Methods: The authors retrospectively reviewed 146 patients who sustained traumatic mandible fractures at a level 2 trauma center over a 5-year period, between January 2012 and December 2016. The authors excluded all patients who did not undergo surgery, underwent operative closed reduction only, sustained other significant maxillofacial injuries, penetrating mechanisms, and other major injuries based on injury severity scores (ISS) over 15. There were 51 patients meeting inclusion criteria. The authors reviewed admission face computed tomography (CT) scans and Panorex x-rays. Patients were divided into early (<72 hours) and late (>72 hours) open reduction with internal fixation (ORIF) groups. The authors reviewed demographics, mechanism of injury, postreduction imaging, and ISS. All statistical analyses were performed using Stata 15. Results: There were 39 males (76%) and 12 females (24%) in the authors' study, with a mean age of 32 years. Twenty-eight patients (55%) underwent early ORIF and 23 patients (45%) underwent late ORIF, with no mortalities. There was no statistically significant difference in ISS between the 2 groups ( P = 0.081). Preoperative face CT scans were performed in 49 patients (96%) and Panorex in 2 patients (4%). Eight patients (16%) had both modalities, with CT face identifying fractures in 5 patients not seen on Panorex, resulting in a change in operative approach. Postreduction imaging was obtained in 33 patients (65%), of whom 26 were Panorex X-rays. These demonstrated adequate reduction in 31 patients (94%) and did not change management in any instance. Complications occurred in 19 patients (37%), of whom there were 11 with uncontrolled pain after 1 week, 6 abscesses, 5 nonunions/malunions, 2 hardware extrusions, and 1 incisional dehiscence. A positive urine drug screen predicted uncontrolled pain ( P < 0.05). There was no statistically significant difference in complications between the 2 groups. Conclusion: The authors' data suggest that CT scans of the face are superior to panoramic radiographs in traumatic mandible fracture evaluation, with no apparent benefit from routine postreduction imaging in detecting complications. Open reduction with internal fixation remains an effective treatment with favorable outcomes, and operative delays > 72 hours do not appear to increase complication rates.